2019
DOI: 10.3389/fimmu.2019.00946
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Natural Killer Cells: Organ-Specific Sentinels of Liver Immune Homeostasis and Physiopathology

Abstract: The liver is considered a preferential tissue for NK cells residency. In humans, almost 50% of all intrahepatic lymphocytes are NK cells that are strongly imprinted in a liver-specific manner and show a broad spectrum of cellular heterogeneity. Hepatic NK (he-NK) cells play key roles in tuning liver immune response in both physiological and pathological conditions. Therefore, there is a pressing need to comprehensively characterize human he-NK cells to better understand the related mechanisms regulating their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
122
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(124 citation statements)
references
References 152 publications
1
122
0
1
Order By: Relevance
“…More NK cells were activated and secreted more OPN in livers from mice on HFDs. The liver is populated by both transient cNK cells and trNK cell subsets that are phenotypically and functionally different . Compared with cNK cells, trNK cells are efficient at producing inflammatory cytokines including IFN‐γ, TNF‐α, and GM‐CSF .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…More NK cells were activated and secreted more OPN in livers from mice on HFDs. The liver is populated by both transient cNK cells and trNK cell subsets that are phenotypically and functionally different . Compared with cNK cells, trNK cells are efficient at producing inflammatory cytokines including IFN‐γ, TNF‐α, and GM‐CSF .…”
Section: Discussionmentioning
confidence: 99%
“…The liver is populated by both transient cNK cells and trNK cell subsets that are phenotypically and functionally different. 10,29 Compared with cNK cells, trNK cells are efficient at producing inflammatory cytokines including IFN-, TNF-, and GM-CSF. 30 Here, we found that trNK cells produced more OPN than cNK cell subsets during diet-induced obesity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the Ltbr ligand (Ltb) was effectively absent in KP1 cells (less than 1.5 TPM in bulk samples and pool-and-split controls from liver colonies). We searched Tabula Muris (40) and found that Ltb is abundantly expressed in hepatic natural killer (NK) cells, the most-prevalent lymphocyte population in the liver (65). Given that NK cell activity is retained or enhanced in athymic nude mice (66), their paracrine communication with KP1 cells is a plausible mechanism for heterogeneous NF-κB pathway activation in the liver.…”
Section: Mifmentioning
confidence: 99%